Implementasi Perhitungan Tarif Bea Masuk, Pajak Pertambahan Nilai Dan Pajak Penghasilan Pasal 22 Terhadap Barang Impor : Studi Kasus Pada PT Gemilang Prima Utama Sentul, Bogor - Kartika, Sri; Riyadi, Rizal; Sipahutar, Mangasa Augustinus (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Today, globalization is experienced by all countries in the world indirectly almost every country runs an open economic system. An open economy is characterized by international trade relations. The fact that every country cannot fulfill its own needs is indeed one of the factors driving the emergence of international trade. Import activity is one form of international trade. PT Gemilang Prima Utama is an importer in Indonesia that imports various kinds of heavy equipment spare parts and accessories. Import activities are subject to taxes, namely Import Duty (BM) Value Added Tax (VAT) and Income Tax (PPh) Article 22 Import. Based on the results of the review at PT Gemilang Prima Utama, the authors draw conclusions on the review of the calculation of Import Duty (BM), Value Added Tax (VAT) and Income Tax (PPh) Article 22 on imported goods at PT Gemilang Prima Utama, namely as follows: 1. Calculation of Import Duty (BM) rates on imported goods carried out by PT Gemilang Prima Utama in accordance with the Minister of Finance Regulation Number 26 / PMK.010 / 2022. 2. The calculation of Value Added Tax (VAT) on imported goods carried out by PT Gemilang Prima Utama is in accordance with Article 7 of Law No. 42 of 2009 and Law of the Republic of Indonesia Number 7 of 2021 concerning Harmonization of Tax Regulations Article 7. The calculation of Income Tax Article (ITA) 22 on imported goods carried out by PT Gemilang Prima Utama is in accordance with the Minister of Finance Regulation Number 41/PMK.010/2022.   Keywords: Import, Import Duty, VAT, Income Tax Article 22 Import, PMK